The Supposed Election of Officers in 1 Cor 11.19: A Response to Richard Last - Brookins, Timothy (New Testament studies, 2014)
This article responds to a recent proposal by Richard Last that 1 Cor 11.19 speaks of the necessity of holding regular ‘elections’ (αἱρέσεις) for the appointment of church officers who would assist in the administration of the Lord's Supper (11.17–34). In addition to exaggerating difficulties inherent in traditional explanations, Last's proposal introduces a number of insurmountable discourse problems, rendering his interpretation more problematic than those he intends to replace. A traditional reading should be retained, in support of which further arguments are here added.